Workforce Adaptation to the Cessation of Motor Vehicle Manufacturing in Australia. Issue 4 (14th October 2016) - Dixon, Janine
Abstract : Over 2016 and 2017, the last of Australia's motor vehicle manufacturing plants will close their doors, retrenching several thousand workers. Agility, the solution to our economic woes, will be the key to recovery. Just how agile will workers need to be? This paper describes a scenario in which there is no "damage" in terms of increased unemployment, facilitated by flexibility in both occupation‐specific real wages and willingness of workers to transition to new occupations and new regions. The scenario identifies occupations and regions into which displaced workers may transition, based on an economy‐wide view of regional industry demands for labour and the skill profiles of the displaced workers.